Pengaruh Free Cash Flow , Collateralizable Assets , Dan Kebijakan Hutang Terhadap Kebijakan Dividen - Christovani Aditya Sidharta, Augustpaosa Nariman (Jurnal Paradigma Akuntansi, 2021)
This study aims to examine the effect of free cash flow, collateralizable assets and debt policy on dividend policy in listed manufacturing companies in Indonesian Stock Exchange period 2016 – 2018. Sample were selected using purposive sampling method with total 45 companies. Data processing techniques using multiple linear regression methods with software Eviews 11. The results of this study indicate that free cash flow has a significant and positive effect on dividend policy, collateralizable assets has a significant and positive effect on dividen policy and debt policy has no effect on dividen policy.